A global change-induced biome shift in the Montseny mountains (NE Spain) - Penuelas, Josep; Boada, Martí (Global Change Biology, 2003)
Shifts in plant species and biome distribution in response to warming have been described in past climate changes. However, reported evidence of such shifts under current climate change is still scarce. By comparing current and 1945 vegetation distribution in the Montseny mountains (Catalonia, NE Spain), we report here a progressive replacement of cold-temperate ecosystems by Mediterranean ecosystems. Beech (Fagus sylvatica) forest has shifted altitudinally upwards by ca. 70 m at the highest altitudes (1600–1700 m). Both the beech forests and the heather (Calluna vulgaris) heathlands are being replaced by holm oak (Quercus ilex) forest at medium altitudes (800–1400 m). This beech replacement has been observed to occur through a progressive isolation and degradation of beech stands. In ‘isolated’ (small and surrounded by holm oaks) beech stands, beech trees are 30% more defoliated, beech recruitment is 41% lower, and holm oak recruitment is three times higher than in ‘continental’ (large and continuous) beech stands. The progressively warmer conditions, complemented by the land use changes (mainly the cessation of traditional land management) are the apparent causes, providing a paradigmatic example of global change affecting distributions of plant species and biomes.
The following values have no corresponding Zotero field: publisher: Blackwell Science, Ltd
Keywords: altitudinal shift; biome replacement; Calluna heathland; climate change; defoliation status; Fagus sylvatica; Land use change; mediterranean forest; Montseny mountains; Quercus ilex; Recruitment; temperate forest